Characteristics of Heavy Metals and Pb Isotopic Composition in Sediments Collected from the Tributaries in Three Gorges Reservoir, China - Bo Gao; Huaidong Zhou; Yong Huang; Yuchun Wang; Jijun Gao; Xiaobo Liu (The Scientific World Journal)
The concentrations, distribution, accumulation, and potential ecological risk of heavy metals (Cr, Cu, Zn, Ni, As, Pb, Cd, and Hg) in sediments from the Three Gorges Reservoir (TGR) tributaries were determined and studied. Pb isotopic compositions in sediments were also measured to effectively identify the potential Pb sources. The results showed that the average concentrations of heavy metals in sediment of TGR tributaries were higher than the local background values of soils and sediments in China. The assessment by Geoaccumulation Index indicated that Cu, Ni, and Hg were at the “slightly polluted” level and Cd was ranked as the “moderately polluted” level in tributary sediments of TGR. The assessment by Potential Ecological Risk Index showed that Hg and Cd were the predominant elements in tributary sediments in TGR. The Pb isotopic ratios in sediments varied from 1.171 to 1.202 for 206Pb/207Pb and from 2.459 to 2.482 for 208Pb/207Pb in TGR. All Pb isotopic ratios in sediments were similar to those from coal combustion, lead ores (the mining activities and smelting process), and cement material, indicating that these anthropogenic inputs may be the main sources for Pb pollution in sediments of TGR tributaries.